Telaah Fenomenologis Patrimonialisme Budaya Politik Terhadap Konflik SunnÃ®-ShÃ®âah Madura - Jatim, Jatim (Koordinatorat Perguruan Tinggi Agama Islam Swasta Wilayah IV Surabaya, 2016)
The article attempts to discover the violence conflict between the SunnÃ® and the ShÃ®âah Muslim communities in Karang Gayam and Bluâuran, Sampang, Madura. The conflict between the two communities has occurred since 2005 to 2013, and has escalated from one event to another. The conflict has caused the expulsion of ShÃ®âah people out of Madura island to the refugeeâs flats of Puspa Agro Sidoarjo on June 20, 2013. Based on the evidences found, the research is intended to study the phenomenon using phenomenological and patrimonial-political-cultural approa-ches. The study finds that the conflict itself has been caused by a set of hatred discourses and accusation of being heretic, which have been intensely propagated by the local religious elites, i.e. kiai against the ShÃ®âah community led by Tajul Muluk. Moreover, the conflict escalation was, among other, due mainly to the strength of patronage relations of the kiais to infiltrate their hegemony and produce the mass to commit violent actions. Incongruously, the power of patronage has been also benefited by the government and many political elites to maintain their political electability and votes. As a result, the government seems to be reluctant to show a firm attitude by enforcing the existing rules to deal with the issue.